Iniciativas de promoção das discussões de gênero e diversidade sexual no contexto acadêmico: um estudo comparativo - Dias, Alfrancio Ferreira (2021)
In this article, we present partial results of the research entitled “Voices of university students on sexual and gender diversity, its relationship with co-education and pedagogical innovation: a comparative study at the University of Madeira (Portugal) and at the Federal University of Sergipe (Brazil). Based on one carried out, we present some reflections on the inclusion of gender and sexual diversity in teacher training developed by UFS, in Brazil and UMa, in Portugal. Methodologically, we adopted a qualitative approach, applying a questionnaire with open questions. We stress the reasons why the research participants consider it important to participate in/in initiatives to include gender and sexual diversity in the academic environment, as well as suggestions for initiatives to be developed in an immediate, medium-range and long-range time. Finally, the arguments analyzed by the graduates show differences between the training given by UMa and UFS regarding the inclusion of discussions on gender and sexual diversity in the  academic  environment, despite also identifying diferences  betweenthese practices in the course on the campus of Itabaiana and in Saint Kitts. We believe it is too early to issue precise opinions on this issue, but we hope that by completing the analysis of all categories of the investigation, it will be possible to rehearse problematizations about these differences.